(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the efficacy of administering dexamethasone through intra-cameral injection in comparison to the conventional application of topical steroids for individuals undergoing phacoemulsification. Study Design: Quasi experimental trial study Place and Duration of Study: This study was conducted at the department of Ophthalmology Ghazi Hospital Dera Ghazi Khan form September 2022 to August 2023. Methods: Eighty patients of age 55-80 years were enrolled in the study and divided into two groups 1 and 2. In group 1 patient were given intra-cameral dexamethasone and in group 2 equal amount of 0.01 ml normal saline was administered. Results: At 1st post-operative day mean IOP in group 1 was 14.75±2.55 and in group 2 was 17.85±2.22. Similarly, at day 7 mean IOP in group 1 was 13.18±2.14 and in group 2 it was 12.44±1.74. In comparison pre operative IOP was in group 1 and 2 was 16.19±2.54 and 12.44±1.74 respectively. Conclusion: Intraoperative inflammation following phacoemulsification surgery can be effectively managed by administering intra-cameral dexamethasone injection, resulting in decreased flare and anterior chamber cells, with comparable impacts on IOP and visual acuity when compared to the use of topical steroids.